Grandparents, grandchildren and the generation in between - Ochiltree, Gay (ACER Press, 2006)
Becoming a grandparent is something that most people look forward to. There isthe joy of the birth and anticipation of the fun the grandparents will have with thenew grandchild, without the responsibility that being a parent involves. However, it is the grandparent's relationship with the generation in between, and events inthat family, which will govern their relationship with their grandchild.